Cost-Benefit Analysis on the use of BIM in the Construction of the Complex Prison in Araçoiaba (Research, Society and Development, 2021)
Nowadays, it’s usual to have costs with rework during the construction process. This can be attributed to problems regarding the coordination across disciplines in a project, and due to problems regarding untrained professionals. In this context, the present study aims to demonstrate and evaluate the use of clash detection tools associated with BIM (Building Information Modeling) Platforms to analyze clash reports and coordinate the model as close to construction as possible. BIM is a process to generate and manage building data that has tools, platforms, and environments to optimize and automatize the process of conflict detections among different projects. Based on this, a case study was conducted in order to verify the benefits brought with the use of the clash detection tool in the management of the construction of the Araçoiaba Prison Complex developed by the coordinator of the construction of this project. The methodology utilized consisted of the analysis of twenty Critical Analysis Report. The main goal of the case study was to verify the cost needed to solve the identified conflicts to run a benefit-cost analysis. The results of the study confirmed the advantages associated with verifying conflicts across disciplines in projects by using BIM Technology.